Bud-neck scaffolding as a possible driving force in ESCRT-induced membrane budding - Mercker, Moritz; Marciniak-Czochra, Anna (Biophysical journal, 2015)
Membrane budding is essential for processes such as protein sorting and transport. Recent experimental results with ESCRT proteins reveal a novel budding mechanism, with proteins emerging in bud necks but separated from the entire bud surface. Using an elastic model, we show that ESCRT protein shapes are sufficient to spontaneously create experimentally observed structures, with protein-membrane interactions leading to protein scaffolds in bud-neck regions. Furthermore, the model reproduces experimentally observed budding directions and bud sizes. Finally, our results reveal that membrane-mediated sorting has the capability of creating structures more complicated than previously assumed.
Gesehen am 08.08.2017